Analisis Risiko Modal Ventura Syariah di Indonesia - Umi Qurrotul Aini; Mugiyati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Venture capital as an alternative financing outside credit banking. Investments made in the form of shares or convertible bonds in the long term, and aimed at business partner companies (PPU), venture capital is a collection of capital originating from investors to be managed professionally by a management company and investment in PPU. Funds invested in venture capital are investment funds that have high risk. This research uses a library or literary study approach. Data collection techniques are carried out through reading and taking notes, as well as managing previous research materials. The aim of this research is to determine the potential risks that will occur and the impact of risks on venture capital. Research results show that venture capital often contributes to helping entrepreneurs develop. So it cannot be denied that venture capital is very prone to losses for both parties.